Integrating design expert insights for achieving market success in new product development - Mohd Rashid, Mohamad Saiful Sazwan; Alli, Hassan; Abdul Rahman, Ahmad Rizal; Kamarudin, Khairul Manami (Universiti Putra Malaysia Press, 2025)
In the competitive landscape of product development, innovation plays a crucial role in creating value and addressing evolving market demands. This study explores the integration of user experience (UX) and knowledge into the product development process, emphasizing their impact on product marketability and success. Drawing on insights from design experts with substantial experience in New Product Development (NPD), the study highlights how understanding user needs, preferences, and experiences informs the creation of market-driven products. By incorporating cognitive, ergonomic factors, and product quality characteristics, designers can enhance product aesthetics and functionality to create a quality product, ultimately increasing purchasing decision. The findings suggest that the collaboration of design experts in the early stages of product development significantly influences product characteristics and improves decision-making. This research demonstrates that leveraging expert knowledge and UX not only drives innovation but also increases the likelihood of creating products that resonate with users and achieve marketability and success.